Placenta percreta with congenital uterine abnormality in a primigravida: A case report - Kervindran, Mohanasundaram; Christine, Lee Mui Fong; Soe, Lwin; Lai, Qi Ji; Harris, Suharjono (Malaysian Medical Association, 2021)
Abnormal placentation is typically seen in patients with risk factors, usually a history of uterine surgery, and follow up for these cases would be tailored accordingly. This a case of placenta percreta in a primigravida with congenital uterine abnormality noted during surgery. Case Description: A 41-year-old primigravida with gestational diabetes mellitus on metformin presented at 20 weeks of pregnancy with acute abdomen without per vaginal bleeding. Physical examination revealed a distended abdomen with generalized tenderness, and bedside scan revealed a viable fetus within uterus with low lying placenta and some free fluid in the abdomen. She was normotensive but tachycardic, with a hemoglobin of 8 g/dL (her booking hemoglobin was 11.3 g/dL). Formal ultrasound was reported as perforated appendicitis. Intraoperatively placenta percreta with uterine rupture was diagnosed, with the entire amniotic sac expelled out. Noted unicornuate uterus with rudimentary horn; patient did not have left ovary and Fallopian tube. Subtotal abdominal hysterectomy was done. The fetus did not survive. HPE was reported as placenta percreta with uterine fibroid. Discussion: An online search revealed less than 10 similar cases being reported, and they mostly were of a younger-age group. This patient also had a history of subfertility for 5 years that was not previously investigated. Due to her age factor, she was referred for detailed scan however she presented 2 weeks before her scheduled appointment with the MFM team. Pregnant primigravida in acute abdomen with free fluid should raise suspicion for possibility of abnormally invasive placenta and congenital uterine abnormality